Pelvic venous disease; knowledge gap - Marie Josee E van Rijn; Clark J Zeebregts (Turkish Journal of Vascular Surgery)
Good quality data is lacking for pelvic venous disease (PeVD) and there are knowledge gaps in several topics. While we know that multiple pregnancies, hormonal factors and compression syndromes are risk factors, less is known about environmental and lifestyle factors. Most studies investigated the effect of coil embolization in relation to pain, but outcomes missing are quality of life (QOL), recurrence, complications, cost- effectiveness and predictors of a good response. There are no studies comparing different embolization techniques and hardly any studies on alternative treatment modalities or pharmacological treatment. It is important to distinguish different symptoms PeVD can cause when reporting patient related outcomes. Most studies use VAS scores, however, there is more to PeVD than pain. Concomitant diseases are common and may impact QoL by itself and must be taken into consideration as well. Finally, there are gaps in patient education and awareness. A scoring system would help in identifying patients. Recently, such a screening score was proposed. In conclusion, research in the field of PeVD is still in its infancy creating gaps in knowledge and awareness. Closing these gaps is essential for PeVD diagnosis and treatment. [Turk J Vasc Surg 2023; 32(0.000): 6-9]